A Short Note on Asteraceae as Traditional Food and Medicinal Plants in Cihanjawar Village, Purwakarta Regency, West Java - Reza Raihandhany; Angga Dwiartama; Rina Ratnasih (School of Life Sciences and Technology, Institut Teknologi Bandung, 2023)
Asteraceae is known as the largest family of flowering plants. Despite some species members being invasive plants, these species are often adopted and utilized by local community groups for food, traditional medicine, and other uses. In our ethnobotanical study of Asteraceae, we identified ways a local Sundanese community group in West Java utilizes a diverse range of species in the family for different purposes. Our study focuses on a Sundanese village called Cihanjawar, located in the regency of Purwakarta, using ethnobotany and ethnomedicine approaches. People of Cihanjawar utilize some species of Asteraceae for food as ‘lalapan’ and traditional medicinal purposes. In-depth, semi-structured interviews with the people of Cihanjawar were conducted to collect primary data regarding the utilization of Asteraceae species as food and traditional medicine. A total of eight species of Asteraceae were found during the field-guided exploration in Cihanjawar Village, which include Acmella paniculata, Ageratum conyzoides, Calyptocarpus vialis, Crassocephalum crepidioides, Dichrocepala integrifolia, Emilia sonchifolia, Erechtites valerianifolia, Sphagneticola trilobata, some of which are considered invasive alien species. The species of A. paniculata, C. crepidioides, E. sonchifolia, Er. valerianifolia is eaten as a raw food (lalapan, Ind.). Then Ag. Conyzoides and C. crepidioides are utilized in traditional medicine. C. vialis, D. integrifolia, and Sphagneticola trilobata are not used by the people of Cihanjawar as food or as traditional medicine.